Oral-Health Related Quality of Life of Children in Two Gulf Countries After Lifting of COVID-19 Restrictions: A Comparative Study - Lena Fahad Alammari; Maram Ibrahim Alenezi; Bashaer Kanaan Almutairi; Rayan Lafi Althafiri; Mohammad Abdul Baseer; Abdul Rahman Dahham AlSaffan; Wasmiya A AlHayyan (Journal of Pharmacy and Bioallied Sciences)
Background: After COVID-19 pandemic, when the restrictions were lifted, it would have impacted the quality of life associated with dental health, particularly in children. Rationale of the present investigation was to evaluate and compare the quality of life related to oral health (OHRQoL) among children aged 5–9 years in Riyadh, Saudi Arabia, and Kuwait following the easing of pandemic restrictions. Materials and Methods: This current descriptive cross-sectional investigation evaluated the parental perception of OHRQoL of their children aged 5–9 years from selected hospitals in Riyadh and Kuwait after the lifting of pandemic restrictions. Parents were administered with Child Oral Health Impact Profile-Short Form (COHIP-SF) questionnaire to assess the OHRQoL of children. The questionnaire elicited responses on oral symptoms, functional well-being, socioeconomic well-being, school environment, and self-image of the children. All the obtained responses were scored and compared between Saudi and Kuwaiti parents by applying appropriate statistical tests. P value of <0.05 was decided for all statistical tests for significance. Results: The parents of total of 718 children (448 male and 270 female) aged between 5 and 9 years responded to the COHIP questionnaire, in which 243 parents were from Kuwait City and 475 were from Riyadh City. A significantly higher overall mean COHIP score was reported by Riyadh City parents than Kuwaiti parents (2.44 ± 0.445 vs. 2.29 ± 0.434, P < 0.001). Kuwaiti parents showed significantly higher scores in school environment and self-image domains than the Riyadh parents. Contrarily, Riyadh’s parents showed significantly higher scores in socioeconomic well-being, functional well-being, and oral symptoms than Kuwaiti parents. Conclusion: In conclusion, the present study showed differences in OHRQoL among children in Kuwait and Riyadh. Gender and age differences in OHRQoL were observed. Furthermore, the present study identified changes in the OHRQoL of children during COVID-19 restrictions and after in Kuwait and Riyadh City.